Fresno County Bar Association Law Day Luncheon: Attorney General John Van de Kamp - Watkins, Howard::::::::: (1987)
Fresno-Merced Counties Legal Services Voluntary Legal Services Program Coordinator Carmen Romero presenting 1987 Outstanding Volunteer Attorney of the Year Award to Dale Ikeda